Behavioral and hormonal studies on Egyptian Baladi goat (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The study was conducted to determine the effect of parity of female goat, social ranking and ovulatory responses of does during seasonal anestrus period by exposure to male effect.Materials and methods: The study was conducted on a flock of Baladi goats at the animal farm of the Faculty of Veterinary Medicine, Zagazig University during November 2014 to January 2015. A total of 54 healthy Baladi goats comprising of 4 males and 50 females aging 12-18 months were used for this study. The goats were raised under indoor raising system, and were released to graze during daylight hours and returned to closed shed. The animals were fed dehydrated alfalfa granules and mixed fodder. The goats were given water ad libitum. Sexual behavioral patterns of both male and female goats were observed. During estrus behavioral resposes shown by the does, blood samples were collected from the goats for the examination of luteinizing hormone (LH). Results: The mounting activity were higher in males in contact with multiparouse females than those of nulliparouse ones. The sexually experienced does induce the activation of L.H hormones leading to stimulation of estrus responses of does. That's why social ranking of does had a significant effect on sexual behavior of bucks when exposed to does during anestrus period. LH hormones secretion in 2nd week in female exposure to males was higher than those of 1st week of exposure at both multiparous and nulliparous females.Conclusion: It concluded that visual, alfactactory, auditory contact with the male stimulate estrus response of anestrus females to be sexually responsive resulting in an increase in the economic gain of goat farm.http://doi.org/10.5455/javar.2016.c146